Toward enhancing the chlorine resistance of forward osmosis membranes: an effective strategy via grafting cyclohexylamine - Yinghua Li (IWA Publishing, 2021)
The forward osmosis (FO) membrane exhibits great performance degradation when contacting with chlorine solutions. The damage of chlorine to membrane material will seriously reduce the lifetime of the membrane and increase the cost of membrane treatment technology. Here, we prepared chlorine-stable membranes by a covalent modification method with cyclohexylamine. The cyclohexylamine observably changed the surface morphology, the roughness (arithmetic average) of the membrane decreased from 22 to 17.2 nm. The addition of cyclohexylamine produced a denser sacrificial layer of short chain polyamide, which made modified membranes possess significantly better chlorine resistance with slightly declined water flux. The water flux of the optimal modified membrane was 10.78 Lm−2 h−1, only 13% less than that of the pristine membrane. Importantly, after 20,000 ppm·h chlorine exposure, the membrane with 1.5 wt% cyclohexylamine had a salt rejection of 77.2% and showed 26.0% lower water flux than pristine TFC (thin film composite) membrane in FO mode. Notably, the grafting membranes could maintain a high performance under acidic chlorination conditions. The membrane with best performance had a salt rejection of 81.6%, exhibiting 24.4% higher salt rejection than pristine membrane with 20,000 ppm·h chlorine exposure at a pH of 4. The cyclohexylamine endowed the FO membrane with better chlorine resistance, making it attractive for the development of chlorine-resistant membrane for environmental and desalination processes. HIGHLIGHTS The addition of cyclohexylamine produced a chlorine-resistant sacrificial layer.; The 1.0 wt% addition of cyclohexylamine did not significantly decrease the water flux of the forward osmosis membrane.; Under acidic conditions, cyclohexylamine could still significantly improve the chlorine resistance of forward osmosis membranes.;